2021
DOI: 10.1177/10436596211057896
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Saudi Community Attitudes Towards Domestic Violence Against Women? A Cross-Sectional Study From Riyadh

Abstract: Introduction: Culture and social norms shape attitudes towards domestic violence against women (DVAW). Attitudes accepting DVAW contribute to violence. There is scarce evidence about community attitudes towards DVAW in Saudi Arabia. The study explores the Saudi community attitudes towards DVAW. Methods: The study utilized a descriptive cross-sectional design using a self-report structured questionnaire to collect socio-demographic data and participants’ attitudes towards DVAW. Results: The study sample include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In one study, singles were shown to have higher positive attitudes towards violence against women compared to married individuals (Tok and Mayda 2021). Selim et al (2022) reported that 19% of married women considered violence against women in the family as normal, 68.2% of single women and 79.5% of divorced women rejected domestic violence. The low scores of those who are married may be due to the fact that in societies influenced by Islamic culture, marriage is considered sacred and the confidentiality of all events/actions within marriage is emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, singles were shown to have higher positive attitudes towards violence against women compared to married individuals (Tok and Mayda 2021). Selim et al (2022) reported that 19% of married women considered violence against women in the family as normal, 68.2% of single women and 79.5% of divorced women rejected domestic violence. The low scores of those who are married may be due to the fact that in societies influenced by Islamic culture, marriage is considered sacred and the confidentiality of all events/actions within marriage is emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while demographic factors may significantly mediate the association between cultural values and IPV, a direct contribution from certain aspects of culture cannot be entirely ruled out. Some of these, such as an emphasis on family honor and a reluctance to discuss intra-familial problems with "outsiders, " have been consistently reported in studies of migrant and ethnic minority women in Western cultures (Hulley et al, 2022) as well as in Asian and African settings (Mshweshwe, 2020;Arisukwu et al, 2021;Selim et al, 2022). Other values that have been reported to contribute to IPV in collectivist settings include notions of self-sacrifice associated with the female gender role (Natal, 2022), acceptance of cultural myths regarding the acceptability of violence among men (Toplu-Demirtas et al, 2022), and exaggerated notions of masculinity and patriarchy (Mshweshwe, 2020;Arisukwu et al, 2021).…”
Section: Relationship Between Individualism-collectivism and Intimate...mentioning
confidence: 99%